The Effect of Clima-Tech on Sustainable Power Supply in Nigeria - Alexander Chinago Budnukaeku; Aloni Clinton; Amadi Dennis Ejike (Innovation in Science and Technology, 2025)
The study “Effect of Clima-tech on sustainable power supply in Nigeria” tends to proffer solution on the challenges limiting sustainable power supply in Nigeria. To achieve this aim, the work classifies the types of power supply available in Nigeria, observes the challenges facing the sector. Of the various power supplies available in Nigeria, this work examines climate supported power supply. Among other things the work observes that climate, Technology and Managerial ability are the major challenges facing sustainable power supply in Nigeria. Climate play a major role in the production of some power supply, therefore such power supply in this work is regarded as climate supported power supply. The effectiveness of such power supply depended on the prevailing climatic condition of the area. Among other things suggested is the transporting of freshwater from the South to the North where hydroelectric powers are situated. This kind of technology will definitely address the issue of low volume of water in the dam for adequate power production. Other suggested solutions include tapping underground water to recharge the dam and to seed cloud for rainfall to occur in the hydroelectric power region. It is also observed that Nigeria lies within the tropics, which is a favourable climatic condition for solar power production and supply because the sunshine duration is always long. It is therefore suggested that cheap but powerful solar boxes should be used in providing power for the people. Geographically, speaking location of Nigeria favours the harvesting of wind energy. The Northern part of the country with few and scanty vegetation, to the roughed middle belt of Nigeria, with hills and mountains, which is breeding ground of wind current between the foot of the mountain and the top of the mountain (Katabatic wind) harness of wind energy will add to the available power in store for distribution. In the South, the land and sea breeze, the open Atlantic Ocean can always provide windy condition for wind farm. This paper opines that if this natural source energy are properly harnessed and properly managed, the issue of inadequate power supply will be a thing of pass.